Impact of Service Quality, Price, and Product Quality on Customer Loyalty through Customer Satisfaction: A Case Study of Shoessimple.id - Dammandtyo Tegar; Rusdi Hidayat Nugroho (International Journal of Economics Development Research (IJEDR), 2024)
The continuous growth of the global economy drives business competition to become increasingly fierce, including the rapid growth of startups. This research will discuss the aspects influencing business competition, namely Service Quality, Price, and Product Quality on Customer Loyalty through Customer Satisfaction. This research employs an associative research type with a quantitative approach, collecting data through questionnaire distribution. The sample consists of 200 respondents of shoessimple.id shoe washing service customers selected using Non-Probability Sampling-Purposive Sampling techniques. Data analysis is conducted using path analysis method with SPSS 2.0 for Windows statistical software.  The research findings indicate that service quality, price, and product quality significantly affect customer satisfaction. Furthermore, customer satisfaction also plays a significant role as an intervening variable mediating the relationship between service quality, price, and product quality with customer loyalty. These findings provide a better understanding of the factors that can enhance customer loyalty in the shoe washing service industry and offer guidance for the management of Shoessimple.id Shoe Washing Service to improve their service quality.